2015
DOI: 10.1371/journal.pntd.0004260
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Poverty as a Driver of Ebola Transmission

Abstract: BackgroundPoverty has been implicated as a challenge in the control of the current Ebola outbreak in West Africa. Although disparities between affected countries have been appreciated, disparities within West African countries have not been investigated as drivers of Ebola transmission. To quantify the role that poverty plays in the transmission of Ebola, we analyzed heterogeneity of Ebola incidence and transmission factors among over 300 communities, categorized by socioeconomic status (SES), within Montserra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 13 publications
0
67
1
1
Order By: Relevance
“…It is important to consider that the real genesis of this preventable outbreak is the combined effect of the legacies of slavery (ie, Maafa 7 ), exploitative colonialism, purposeful underdevelopment, structural adjustment, resource extraction, illicit financial flows, poverty, gender violence, and enabled civil war. 8,9 When viewed through this lens, even the revised case fatality of 55·6% is misleading: we estimate the true case fatality of EVD to be less than 10% when patients have access to a high-level intensive care unit-notably, all repatriated Americans infected with Ebola virus survived. 10 In summary, although highly skillful work-like that of Timothy and colleaguesis integral to improved understanding of viral transmission dynamics, such virtuosity should not obscure recognition of the structural determinants of epidemics.…”
Section: The Genesis Of the Ebola Virus Outbreak In West Africamentioning
confidence: 95%
“…It is important to consider that the real genesis of this preventable outbreak is the combined effect of the legacies of slavery (ie, Maafa 7 ), exploitative colonialism, purposeful underdevelopment, structural adjustment, resource extraction, illicit financial flows, poverty, gender violence, and enabled civil war. 8,9 When viewed through this lens, even the revised case fatality of 55·6% is misleading: we estimate the true case fatality of EVD to be less than 10% when patients have access to a high-level intensive care unit-notably, all repatriated Americans infected with Ebola virus survived. 10 In summary, although highly skillful work-like that of Timothy and colleaguesis integral to improved understanding of viral transmission dynamics, such virtuosity should not obscure recognition of the structural determinants of epidemics.…”
Section: The Genesis Of the Ebola Virus Outbreak In West Africamentioning
confidence: 95%
“…The association between poverty and HIV/AIDS is best exemplified by the situation in Africa (Kalichman et al 2005; Tladi 2006; Mbirimtengerenji 2007; Nattrass 2009; Thurlow et al 2009; Fox 2010; Shisana et al 2010; Tsai et al 2013). Even some of the serious global viral diseases like Ebola and Dengue have been linked to poverty (Khun and Manderson 2008; Fallah et al 2015). Association between poverty and infectious diseases is not present only in Africa but even in Europe, India, China, Latin America and the USA (Jackson et al 2006; Riley et al 2007; Silveira et al 2008; Gryseels et al 2009; Hotez 2010; Hotez and Gurwith 2011; Cooper et al 2012; Dowd et al 2012; Hotez et al 2012; Karan et al 2012; Oxlade and Murray 2012; Bhutta et al 2014; Hotez et al 2014; Yang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the positive association between crowding and EVD transmissibility is also observed at a lower level of administrative unit cannot be inferred from this analysis. Fallah et al used individual data on EVD cases and their contacts and determined SES-stratified measures of transmission [12]. They found that cases from middle and low SES communities caused significantly more secondary cases than infected individuals from high SES communities.…”
Section: Discussionmentioning
confidence: 99%
“…We may also use these data to quantify population-level risk factors for EVD transmission. Demographic or behavioural factors such as crowding and high population density, low socioeconomic status (SES), unsafe burials or poor sanitation but also climate effects might have contributed to enhanced EVD transmission in West Africa, but these effects have been assessed only in a limited number of studies [1,7,11,12]. In the context of recurrent infectious diseases, increased human mobility and globalisation the quantification of subnational spread of EVD and the investigation of factors related to the spread might provide insights that could improve epidemic management in the future [5].…”
Section: Introductionmentioning
confidence: 99%